Inside a Construction Machine - Greaves, Keith (Danbury, CT Grolier Educational, 2001)
Each book in this series gives the reader the history of its subject, working machinery as well as a glimpse into the future.
5 - 9
Keywords: Building; Machinery; Earthmoving machinery